The Design of the Information System of New Student Admission - Zuriati Zuriati (Politeknik Negeri Lampung, 2012)
This paper is about the design of information system for processing new student admission (SIPMB). Manual system, such as using new student admission book, has been implemented to process new student admission information. This method has generated various problems, such as data redundancy, inefficient data organization, and insufficient time in conducting sequence access the score. It makes the student report expressed by pass the selection. The information system is designed by using SDLC method. There are four stages of SDLC method: analyzing, designing, implementing and maintaining. In addition, admission test of SIPMB was conducted.Â Keywords: database, information system,Â SDLC.